Within-Individual Effects of Dropping out of School on Violent Victimization Among Serious Adolescent Offenders - Na, Chongmin (Journal of interpersonal violence, 2022)
Despite a recent decrease in both school dropout and victimization rates, many harsh and exclusionary school policies continue to push school-aged adolescents out of school. This study combines two research areas?school dropout and violent victimization?by investigating if dropping out of school increases the chance of violent victimization. It is hypothesized that a change in the opportunity structure associated with risky lifestyles and routine activities accounts for the link between school dropout and violent victimization. Drawing on longitudinal panel data collected from a relatively homogenous sample of 1354 serious adolescent offenders who are predominantly minorities (75%) and males (86%) and fixed-effects models which enhance the causal validity of the findings by using the same individuals as their own counterfactuals over time, this study shows that dropping out of school leads to the perpetuation of violent victimization, primarily due to a change in the opportunity structure associated with risky lifestyles and routine activities. By uncovering the pathway between school dropout and victimization, this study contributes to the knowledge base on the impact of school dropouts, the source of violent victimization, and the causal mechanism underlying the link between dropping out of school and violent victimization?all of which are relatively understudied despite their significant implications for theory and policy.